Using Cone Beam Computed Tomography in surgical orthodontic treatment of impacted maxillary canines - a case report - Jelena Elez; Slavoljub Tomic; Tanja Ivanovic; Jelena Krunic (Биомедицинска истраживања, 2025)
Introduction: The purpose of this case report was to present a surgical-orthodontic treatment of bilaterally impacted maxillary canines using Cone Beam Computed Tomography (CBCT). Case report. A 16-year-old girl accompanied by parents was admitted to the Specialist Center for Dentistry, Faculty of Medicine Foča, for orthodontic consultation related to aesthetic reasons. Clinical examination revealed the existence of deciduous canines on both sides of maxilla and palpable a tooth-like structure at the level of root of the maxillary right canine. The maxillary left permanent canine was neither visible nor palpable. CBCT analysis showed bilateral impaction of upper canines: the crown of maxillary right canine was positioned centrally in the alveolar processus, while the maxillary left canine was palatally impacted. The treatment plan included combined surgical-orthodontic treatment: fixed orthodontic appliance with standard conventional metal braces, extraction of both deciduous canines and surgical release of impacted permanent canines using closed eruption technique. Favorable clinical results were observed within nine months after initiation of treatment. After two years canines erupted at proper position in dental arch, reaching the occlusal plane with a present of harmonious soft tissue and an adequate zone of keratinized gingiva around teeth. Conclusion: The impaction of maxillary canines is frequent condition which requires a multidisciplinary treatment approach by orthodontist and oral surgeon, and also a motivated patient. The use of CBCT can increase success of the therapy with the proper localization of impacted canines and surrounding anatomical structures.
Keywords: upper canine; impaction; surgical-orthodontic treatment; CBCT